Effect of nanocurcumin supplementation on the severity of symptoms and length of hospital stay in patients with COVID‐19: A randomized double‐blind placebo‐controlled trial. (12th January 2022) - Honarkar Shafie, Elaheh; Taheri, Fateme; Alijani, Neda; Okhovvat, Ahmad Reza; Goudarzi, Razieh; Borumandnia, Nasrin; Aghaghazvini, Leila; Rezayat, Seyed Mahdi; Jamalimoghadamsiahkali, Saeidreza; Hosseinzadeh‐Attar, Mohammad Javad
Abstract: It has been more than a year since the outbreak of COVID‐19, and it is still the most critical issue of the healthcare system. Discovering effective strategies to treat infected patients is necessary to decrease the mortality rate. This study aimed to determine the effects of nanocurcumin on the severity of symptoms and length of hospital stay (LOS) in COVID‐19 patients. Forty‐eight COVID‐19 patients were randomly assigned into nanocurcumin ( n = 24) and placebo ( n = 24) groups receiving 160 mg/day nanocurcumin or placebo capsules for 6 days. Mean differences of O2 saturation were significantly higher in patients who received nanocurcumin supplements ( p = 0.02). Also, nanocurcumin treatment significantly reduced the scores of domains 3 and 4 and the total score of Wisconsin Upper Respiratory System Survey (WURSS‐24), indicating milder symptoms in the treatment group ( p = 0.01, 0.03, and 0.01 respectively). Besides, the LOS in curcumin groups was lower than in the placebo group, although the difference was not statistically significant (6.31 ± 5.26 vs. 8.87 ± 8.12 days; p = 0.416). CBC/differentiate, hs‐CRP level and the pulmonary involvement in CT scan were not different between the two groups. As nanocurcumin can be effective in increasing O2 saturation and reducing the severity of symptoms in COVID‐19 patients, it could probably be used as a complementary agent to accelerate the recovery of patients.